Insecurity and community leadership in Imo State - Ngurukwem, C. C.; Adida, F. A.; Nwosa, C. U. (Journal of Research in Adult and Continuing Education, 2023)
This paper on insecurity and community leadership in Imo state is born out of the enormous security challenges in Imo State and the need to reorient and deepen knowledge and skills of community leaders for better performance in dynamic environment. The paper espoused insecurity in Imo state including killings by unknown gun men, kidnapping for ransom, arson, banditry, poverty, unemployment among others, all of which reflect deteriorating socioeconomic, political and livelihood crises in the state. Noticeable too was the ineffectiveness of community leaders in stemming the menace. Arising from review of relevant literature and theories, is the recognition of situational variables and leadership competencies as essential ingredients in leading in a dynamic environment.The paper observed that community leaders have not being sufficiently equipped with the necessary competencies   to play the leadership role expected of them during crises. It therefore recommends capacity building for leadership competencies needed to mingle situational variables with followers need for leadership. It also recommends regular leadership training for community leaders and in and out-of-school training for both young and old whether in leadership position or not to build a reservoir of competent leaders in our communities.
Keywords: Security; leadership; competencies; community development